2010
DOI: 10.17925/eoh.2010.06.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Use of Internet-based Survivorship Care Plans

Abstract: Over the past decade, the world has demonstrated an increased interest in and awareness of the unique needs of cancer survivors. Survivorship care plans are a communication tool intended to provide guidelines for the healthcare of survivors as they complete active cancer care, and for the duration of their lives. The Internet represents a unique way to communicate with cancer survivors, and data from several groups indicate that increasing numbers of survivors both desire information about their care and seek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Partially driven by an attempt to offer an economically viable solution to the creation of care plans, the US has led the way in creating free of charge web-based SCP tools for use by cancer survivors, their clinicians and family/friends. A survey of HCPs in the USA reported high levels of satisfaction with web-based SCP tools [11], and it has been suggested that they could 'provide essential information to all cancer survivors worldwide' [12] (p.12). However, cultural differences may impact on the acceptability of these tools for use in other countries.…”
mentioning
confidence: 99%
“…Partially driven by an attempt to offer an economically viable solution to the creation of care plans, the US has led the way in creating free of charge web-based SCP tools for use by cancer survivors, their clinicians and family/friends. A survey of HCPs in the USA reported high levels of satisfaction with web-based SCP tools [11], and it has been suggested that they could 'provide essential information to all cancer survivors worldwide' [12] (p.12). However, cultural differences may impact on the acceptability of these tools for use in other countries.…”
mentioning
confidence: 99%
“…Internet-based SCPs may have particular importance for engaging select groups of YAS as compared with survivors of other adult cancers who used Internet-based SCPs over the same time period, a higher proportion of YAS were male, of minority status, and live outside the United States. 44 Regarding treatment, a higher proportion of YAS who used the resource were treated with chemotherapy and bone marrow transplant. YAS, especially those with high treatment intensity will require more years of ongoing survivorship care as well as personalized screening for late effects and subsequent malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Those plans were the ones designed by livestrong (United States) 25,40,41 and the ncsi (United Kingdom) 27,29,42 , organizations that have been involved in survivorship care planning for longer than most others. As a result, they have been able to conduct repeated evaluations 25,27,29,[40][41][42][43][44][45][46][47][48][49] and to make changes to their scps and delivery processes based on the results of those evaluations.…”
Section: Evaluations Of Scpsmentioning
confidence: 99%